Impact of the solar wind dynamic pressure on the field-aligned currents in the magnetotail: cluster observation - Cheng,ZW; Shi,JK; Torkar,K; Lu,GP; Dunlop,MW; Carr,CM; Reme,H; Dandouras,I; Fazakerley,A (JGR: Space Physics, 2021)
We statistically investigate the influence of the solar wind dynamic pressure (SW Pdyn) on the field-aligned currents (FACs) in the magnetotail with 1,492 FAC cases from July to October in 2001 and 2004, which covers 74 Cluster crossings of the plasma sheet boundary layer (PSBL) in both storm time and non-storm time. The FAC density in the magnetotail is derived from the magnetic field data with the four-point measurement of Cluster, and the SW Pdyn is taken from ACE data. The results indicate the FAC density becomes stronger with increasing SW Pdyn. The statistics show that the FAC occurrence increased monotonically with SW Pdyn in the three levels (Weak: SW Pdyn < 2 nPa; Medium: 2 nPa ≤ SW Pdyn ≤ 5 nPa; Strong: SW Pdyn > 5 nPa). The FAC density increased with increasing SW Pdyn, while its footprint (invariant latitude, ILAT) in the polar region decreased with increasing SW Pdyn. The response of the FAC to SW Pdyn in the magnetotail had a north-south hemispheric asymmetry. The FAC density had a better correlation with SW Pdyn in the Northern hemisphere, while the footprint had a better correlation with SW Pdyn in the Southern hemisphere. Possible underlying mechanisms for our results are analyzed and discussed. However, it requires more observations and simulation studies to find out the mechanism of north-south asymmetry.